Do the cognitive and neural mechanisms underlying inattention differ between very preterm and term-born children? - Tellett, Jennifer (2016)
Background: Compared with their term-born peers, school aged children born very preterm (≤32 weeks gestation) are at increased risk of inattention. It remains unclear whether the cognitive and neural mechanisms underlying inattention are the same in both very preterm and term-born children. Aims: The aim of this study was to determine whether the cognitive and neural mechanisms underlying inattention differ between term-born and very preterm children. Chapter 3 explored cognition, while Chapters 4 & 5 explored neural processing in terms of event-related potentials (ERPs) and frequency analysis of functional connectivity respectively, to identify mechanisms underlying inattention. Method: A sample of 65 children born very preterm (≤32 weeks gestation) aged 8-11 years was recruited. A comparison group of 48 term-born peers (≥37 weeks gestation) matched for inattention symptoms using the parent-rated Strengths and Weaknesses of ADHD and Normal behaviour (SWAN) questionnaire was selected for comparison. All children were asked to complete neurocognitive tests to assess basic cognitive processes, executive function and sustained attention. Electroencephalography (EEG) was recorded from a sub-sample of children (very preterm n=43; term-born n=40) while they completed a sustained attention task. The contingent negative variation ERP component and theta and alpha frequency changes following the cue stimulus were derived from the EEG as neural indices of response preparation. Similarly, following the presentation of cued and uncued target stimuli, the P1, P2, and P3 ERP components were derived from the EEG as neural indices of stimulus detection, stimulus categorisation, and evaluation of task-relevance respectively. Results: In both groups, more severe parent-rated inattention on the SWAN was predicted by poorer verbal and visuo-spatial short term memory, visuo-spatial working memory, and greater response time variability, and by smaller amplitude of the P2 ERP to uncued targets at the neural level. In children born very preterm only, slower motor processing speed, and smaller theta increases at the neural level, predicted more severe parent-rated inattention. Similarly, in term-born children only, shorter P2 ERP latencies to all targets predicted more severe parent-rated inattention. Conclusions: In sum, the cognitive and neural mechanisms underlying inattention in term-born and very preterm children were partially overlapping, but some mechanisms were unique to only one group. These results present candidate mechanisms that may be useful for the identification of children at risk for inattention, and as potential targets for intervention.